The Adsorptive Removal of Rhodamine 6G Dye from Aqueous Solution by Using Poly (Fumaric Acid-Co-Acrylic Acid) Hydrogels - Wissam L. Benyan (Journal of Global Pharma Technology, 2016)
The removal of rhodamine 6G from aqueous solutions was achieved by adsorption using poly (fumaric acid-co-acrylic acid) as adsorbent surface. Several variables that affect the adsorption were studied including adsorbent dosage, contact time, pH, temperature and ionic strength. The results indicate that hydrogel has a strong capability of removing rhodamine 6G dye directly from aqueous solutions. The equilibrium adsorption data is analyzed using three common adsorption models: Langmuir, Freundlich and Temkin. The Thermodynamic parameters ΔH, ΔG and ΔS are calculated for the adsorption rhodamine 6G onto hydrogel.Keywords: Hydrogels, Rhodamine6G, Adsorption, Isotherms, Thermodynamic.